The Effects of Technology Entrepreneurship on Customers and Society: A Case Study of a Spanish Pharmaceutical Distribution Company - Muñoz, Rosa M.; Sánchez de Pablo, Jesús D.; Peña, Isidro; Salinero, Yolanda (Frontiers in Psychology, 2016)
The main purpose of this paper is to provide an understanding, within the field of corporate entrepreneurship, of the various factors that enable technology entrepreneurship in established firms and its principal effects on customers and society. The paper reports on a case study regarding technology entrepreneurship in a Spanish company whose activity is pharmaceutical distribution. This company has been able to overcome the consequences of the worldwide crisis and start an innovative process which includes the installation of new Information Technology (IT) and an investment of 6 million Euros. It is, in this respect, a model to imitate and the objective of this paper is therefore to discover the managers’ entrepreneurial orientation characteristics which have made this possible, along with the organizational and social effects resulting from the process. We verify that entrepreneurial orientation is present in this company and that the development of new IT has important effects on customers and the population.